OLIY TA’LIM MUASSASALARI TALABALARINING TARBIYAVIY JARAYONLARINI TASHKIL ETISHNING PEDAGOGIK-PROFILAKTIK AHAMIYATI - Siddikov, X.T. (SCIENCE and SOCIETY, 2022)
In this article, there are given the organization of the educational and pedagogical process with students of higher educational institutions, the formation of methodological guidelines of educational significance, ways to overcome speech problems between teachers and students.